Convulsive Status Epilepticus Induced by Electroconvulsive Therapy in a Patient with Major Depression - Emilie Wieben; Marianne Juel Kjeldsen; Claus H. Sørensen (Case Reports in Psychiatry)
Electroconvulsive therapy (ECT) is a well-known, safe, and efficient treatment for a variety of psychiatric diseases. We present here an unusual case of a 34-year-old patient with major depression, who developed convulsive status epilepticus persistent for eight days in connection to her first ECT—a very uncommon but serious complication. The patient was, prior to ECT treatment, treated with lithium carbonate and clomipramine for her depression. Six years prior to the ECT, the patient had experienced a convulsive syncope resulting in traumatic subarachnoid haemorrhage. This case emphasizes the importance of medical recording to detect possible risk factors when considering ECT treatment.